ERROR ANALYSIS OF USING SIMPLE PRESENT TENSE IN STUDENTS WRITING DESCRIPTIVE TEXT AT THE TENTH GRADERS OF SMKN 2 KUDUS - Syahdanny, Bintang Arief (SIMPLE: International Journal of English Education, 2023)
The purpose of this study was to identify and describe the factors of student errors in using the simple present tense in writing descriptive text by class X students of SMK N 2 KUDUS. The researcher took 15 respondents from the lowest rank in the class as respondents from the document, and 5 respondents from the descriptive text results who made the most errors as respondents from the interview.The research design is a qualitative design. Data were collected from descriptive texts made by respondents as document analysis and interviews. Then the researcher analyzed and classified the errors in the student's work based on the types of errors according to Dulay (1982) which consisted of four categories, namely Omission, Misformation, addition, and misordering. To find out the factors of student error, the researcher analyzed the results of the respondents' interviews with Carelessness, Translation, and First Language. From the results of the study, the researcher found 45 errors in analyzing the simple present tense in writing descriptive text. The most common types of errors in analyzing are 25 errors in misformation errors, and the percentage is 55.5%. There are 14 mistakes in omission, and the percentage is 31.1%. Addition errors and misordering errors are at least 3 errors, and the percentage is 6.7%. The researcher found factors causing errors in the use of the simple present tense, consisting of carelessness or carelessness 28 errors or 80%, translation 6 errors or 17.1%, and first language at least one error, the percentage is 2.9%.